Children's surgery: a national survey of consultant clinical practice. Issue 5 (17th October 2012) - Mason, David G; Shotton, Hannah; Wilkinson, Kathleen A; Gough, Michael J; Alleway, Robert; Freeth, Heather; Mason, Marisa
Abstract : Objectives: To survey clinical practice and opinions of consultant surgeons and anaesthetists caring for children to inform the needs for training, commissioning and management of children's surgery in the UK. Design: The National Confidential Enquiry into Patient Outcome and Death (NCEPOD) hosted an online survey to gather data on current clinical practice of UK consultant surgeons and anaesthetists caring for children. Setting: The questionnaire was circulated to all hospitals and to Anaesthetic and Surgical Royal Colleges, and relevant specialist societies covering the UK and the Channel Islands and was mainly completed by consultants in District General Hospitals. Participants: 555 surgeons and 1561 anaesthetists completed the questionnaire. Results: 32.6% of surgeons and 43.5% of anaesthetists considered that there were deficiencies in their hospital's facilities that potentially compromised delivery of a safe children's surgical service. Almost 10% of all consultants considered that their postgraduate training was insufficient for current paediatric practice and 20% felt that recent Continued Professional Development failed to maintain paediatric expertise. 45.4% of surgeons and 39.2% of anaesthetists considered that the current specialty curriculum should have a larger paediatric component. Consultants in non-specialist paediatric centres were prepared to care for younger children admitted for surgery as emergencies than those admitted electively. Many of the surgeons and anaesthetists had <4 h/week in paediatric practice. Only 55.3% of surgeons and 42.8% of anaesthetists participated in any form of regular multidisciplinary review of children undergoing surgery. Conclusions: There are significant obstacles to consultant surgeons and anaesthetists providing a competent surgical service for children. Postgraduate curricula must meet the needs of trainees who will be expected to include children in their caseload as consultants. Trusts must ensure appropriate support for consultants to maintain paediatric skills and provide the necessary facilities for a high-quality local surgical service.